Localisation of Lactate Transporters in Rat and Rabbit Placentae. (23rd October 2016) - Moore, Nigel P.; Picut, Catherine A.; Charlap, Jeffrey H.
Abstract : The distribution of monocarboxylate transporter (MCT) isoforms 1 and 4, which mediate the plasmalemmal transport ofl -lactic and pyruvic acids, has been identified in the placentae of rats and rabbits at different ages of gestation. Groups of three pregnant Sprague-Dawley rats and New Zealand White rabbits were sacrificed on gestation days (GD) 11, 14, 18, or 20 and on GD 13, 18, or 28, respectively. Placentae were removed and processed for immunohistochemical detection of MCT1 and MCT4. In the rat, staining for MCT1 was associated with lakes and blood vessels containing enucleated red blood cells (maternal vessels) while staining for MCT4 was associated with vessels containing nucleated red blood cells (embryofoetal vessels). In the rabbit, staining for MCT1 was associated with blood vessels containing nucleated red blood cells while staining for MCT4 was associated with vessels containing enucleated red blood cells. Strength of staining for MCT1 decreased during gestation in both species, but that for MCT4 was stronger than that for MCT1 and was consistent between gestation days. The results imply an opposite polarity of MCT1 and MCT4 across the trophoblast between rat and rabbit.